2007
DOI: 10.1109/tasc.2007.897909
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2G HTS Multifilamentary Conductor Design for AC Applications

Abstract: 2G HTS wires need substantial development to allow ac applications with acceptable losses in ac magnetic fields perpendicular to the tape plane. Filament transposition is necessary to avoid large coupling currents and also to insure a uniform current flow through all the filaments, both of which are essential to minimize ac losses. Conductor twisting solves only the first part of the problem and is not really practical in a tape-shaped wire needing to be wound for instance into compact coils of various shapes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The densities of the materials at room temperature are used. It is found that the Cu layer in the conductor has a RRR ∼35 [24]. Thus when using the properties from Cryocomp, Cu with RRR = 35 in zero magnetic field is set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The densities of the materials at room temperature are used. It is found that the Cu layer in the conductor has a RRR ∼35 [24]. Thus when using the properties from Cryocomp, Cu with RRR = 35 in zero magnetic field is set.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the substrate acts as a stabilizer during the quench. It is actually the case for the SS-SS sample, as the resistivity of the NiW substrate is lower than that of SS (table A.1 and [24]). Recent effort shows the possibility of having Cu substrates for YBCO coated conductors [25,26].…”
Section: Implications For Conductor Design From the Quench Behaviour ...mentioning
confidence: 90%
“…For AC applications of coated conductors, high conductivity or superconducting regions between the filaments would increase coupling losses. 26,27 By using multiple depositions, without an interim thermal treatment, the coffee-ring effect is strongly reduced due to an increased amount of deposited material.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…Ideally, the filaments should also be transposed regularly along the conductor. 25,27 The ability to over-print multiple layers with any chosen pattern at high resolution could allow this to be achieved much more costeffectively by ink-jet printing than conventional mechanical methods. 27 Previous reports mention the use of inkjet printing for the deposition of buffer layer structures using organic solvents, while for YBCO there have been very few reports of ink-jet printing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation